AKTIVITAS ANTIDIABETES EKSTRAK ETANOL DAUN ILER (Plectranthus scutellarioides (L.) R.Br.) PADA TIKUS PUTIH GALUR WISTAR DENGAN METODE INDUKSI ALOKSAN - Yasmiwar Susilawati; Ahmad Muhtadi; Moelyono Moektiwardoyo; Putri Churnia Arifin (Farmaka, 2016)
Based on WHO data, in 2014  total of diabetic patient in Indonesia reach 9 million. In addition to synthetic drugs, traditional medicine widely used by diabetic patients. Research of several species from Plectranthus genus showed that Plectranthus amboinicus and P. esculentus have antidiabetic activity in rat. Therefore, it is necessary to do antidiabetic activity research and its effective dose of plants iler (Plectranthus scutellarioides (L.) R.Br) which derived from the same genus and has been used empirically as oral antidiabetic. Antidiabetic activity test conducted using white male Wistar rats which given diabetogen alloxan. Rat who had developed diabetes later given different dose of iler leaves ethanol extract and glibenclamide 0,5 mg/kgBB as a positive control. Blood glucose level was measured using amperometric method utilizing enzymatic reaction of glucose dehydrogenase which measured by glucometer. As a result, a dose of 200 mg / kg dose had the highest antidiabetic activity, followed by a dose of 300 mg / kg, the percentage decrease in relative blood glucose are 21,52% and 3,64% respectively, but a dose of 100 mg / kg didn’t have antidiabetic activity. Antidiabetic activity of 200 mg/kg dose of extract didn’t have any significant difference with glibenclamide, which has percentage decrease in relative blood glucose 21,35%.